The Analysis of the Effect of Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) on Stock Prices (Empirical Study on Food and Beverage Department Manufacturing - Yustinus Rawi Dandono; Desika Andriani; Arizal Azhari; Vandra Angelica (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
to determine the partial and simultaneous effects of NPM, DER, and EPS on the stock prices of manufacturing firms in the food and beverage industry. For this quantitative research, secondary data sources were the Food and Beverage Department Manufacturing Companies' Financial Statements published in the IDX. Purposive sampling is the technique used for sampling. The t-test, F-test, and multiple linear analysis tests were used in this study's testing. The results of the partial study (t-test) showed that the stock prices of food and beverage manufacturing companies listed on the Indonesia Stock Exchange were positively and significantly impacted by NPM, DER, and EPS. It concurrently demonstrated that the stock prices of the Food and Beverage Manufacturing Companies listed on the IDX were positively and significantly impacted by NPM, DER, and EPS, either separately or in combination..